Key Data-Based Church Growth in Indonesia From Evangelical Perspective and Critical Review of Them - Wahyoe Rita Wulandari (Green Publisher Indonesia, 2022)
The datas which is contained in the books of church growth are mostly non-empirical research, on the other hand only raises subject of motivational, hope & promises and apologetic figures. Empirical research approach on the theme or theology of church growth produces data with factual figures. Bilangan Research Center (BRC) is an empirical research institute that provides relevant, valid and current reference data on Christian spirituality and church growth. Spirituality and church growth are discussed using a national-level empirical research database. This paper examines the BRC from an evangelical perspective and critiques its findings from an ecumenical perspective.